Response of the human detrusor to stretch is regulated by TREK‐1, a two‐pore‐domain (K2P) mechano‐gated potassium channel. (21st May 2014) - Lei, Qi; Pan, Xiao‐Qing; Chang, Shaohua; Malkowicz, S. Bruce; Guzzo, Thomas J.; Malykhina, Anna P.
Abstract : Key points: Mechano‐gated two‐pore‐domain potassium (K2P ) channels are expressed in the human bladder, with TREK‐1 being the predominant functional subunit. TREK‐1 channels in bladder smooth muscle are activated by membrane stretch and negative pressure applied to the patch pipette. Inhibition of TREK‐1 channels in the human detrusor significantly delays relaxation of bladder smooth muscle and triggers small‐amplitude spontaneous contractions in response to stretch. Application of negative pressure to cell‐attached patches (–20 mmHg) causes a 19‐fold increase in the open probability ( NP o ) of human TREK‐1 channels. l ‐Methionine (1 mm ) dramatically decreases the NP o of TREK‐1 channels from 0.045 ± 0.003 to 0.008 ± 0.001 ( n = 8, P ≤ 0.01). Addition of arachidonic acid (10 μm ) increases the open probability of methionine‐inhibited unitary currents up to 0.43 ± 0.05 at 0 mV ( n = 9, P ≤ 0.05). TREK‐1 channels may serve as a promising pharmacological target for bladder dysfunction in humans. Abstract: The mechanisms of mechanosensitivity underlying the response of the human bladder to stretch are poorly understood. Animal data suggest that stretch‐activated two‐pore‐domain (K2P ) K + channels play a critical role in bladder relaxation during the filling phase. The objective of this study was to characterize the expression and function of stretch‐activated K2P channels in the human bladder and to clarify their physiological role in bladder mechanosensitivity. Gene and protein analysis of the K2P channels TREK‐1, TREK‐2 and TRAAK in the human bladder revealed that TREK‐1 is the predominantly expressed member of the mechano‐gated subfamily of K2P channels. Immunohistochemical labelling of bladder wall identified higher levels of expression of TREK‐1 in detrusor smooth muscle cells in comparison to bladder mucosa. Functional characterization and biophysical properties of the predominantly expressed member of the K2P family, the TREK‐1 channel, were evaluated by in vitro organ bath studies and the patch‐clamp technique. Electrophysiological recordings from single smooth muscle cells confirmed direct activation of TREK‐1 channels by mechanical stretch and negative pressure applied to the cell membrane. Inhibition of TREK‐1 channels in the human detrusor significantly delayed relaxation of the stretched bladder smooth muscle strips and triggered small‐amplitude spontaneous contractions. Application of negative pressure to cell‐attached patches (–20 mmHg) caused a 19‐fold increase in the open probability ( NP o ) of human TREK‐1 channels.l ‐Methionine (1 mm ), a specific TREK‐1 inhibitor, dramatically decreased the NP o of TREK‐1 channels from 0.045 ± 0.003 to 0.008 ± 0.001 ( n = 8, P ≤ 0.01). Subsequent addition of arachidonic acid (10 μm ), a channel opener, increased the open probability of methionine‐inhibited unitary currents up to 0.43 ± 0.05 at 0 mV ( n = 9, P ≤ 0.05). The results of our study provide direct evidence that the response of the human detrusor to mechanical stretch is regulated by activation of mechano‐gated TREK‐1 channels. Impaired mechanosensation and mechanotransduction associated with the changes in stretch‐activated K2P channels may underlie myogenic bladder dysfunction in humans.